QoE/QoS-aware LTE downlink scheduler for VoIP with power saving. (May 2015) - Mushtaq, M. Sajid; Fowler, Scott; Mellouk, Abdelhamid; Augustin, Brice
Abstract: The emerging and fastest growing multimedia services such as Skype, GTalk and interactive video gaming have created new challenges for wireless communication technologies, especially in terms of resource allocation and power optimization of User Equipments (UEs). The efficient resources and the power optimization are very important in the next communication systems because new multimedia services are more resource and power hungry. Having more traffic flow in the downlink as compared to the uplink, the resource allocation schemes in the downlink are more important than those in the uplink. In this paper, we have proposed a new downlink scheduling scheme, known as Quality-aware DRX (Q-DRX) Scheme, for Long Term Evaluation (LTE) wireless networks that not only improves the Quality of Service (QoS) to satisfy the user׳s experience of multimedia services but also saves the UE׳s power by using the Discontinuous Reception (DRX). This paper investigates how the different durations of DRX Light and Deep Sleep cycles affect the QoS and influence the Quality of Experience (QoE) of end users, in the context of Voice over IP (VoIP) traffic delivery over the LTE wireless network. The performance of the Q-DRX scheme is evaluated with traditional scheduling schemes, in the perception of the following important parameters, System Throughput, Throughput Fairness Index, Packet Loss Rate and Packet Delay. Our proposed Q-DRX Scheme successfully minimized the packet׳s delay and packet׳s loss by considering the key parameters of QoS with fair resources distribution among the UEs to achieve a high satisfaction level.